Multiple pathways coordinate assembly of human mitochondrial complex IV and stabilization of respiratory supercomplexes - Lobo‐Jarne, Teresa (EMBO J, 2020)
Mitochondrial respiratory chain complexes I, III, and IV can associate into larger structures termed supercomplexes or respirasomes, thereby generating structural interdependences among the individual complexes yet to be understood. In patients, nonsense mutations in complex IV subunit genes cause severe encephalomyopathies randomly associated with pleiotropic complex I defects. Using complexome profiling and biochemical analyses, we have explored the structural rearrangements of the respiratory chain in human cell lines depleted of the catalytic complex IV subunit COX1 or COX2. In the absence of a functional complex IV holoenzyme, several supercomplex I+III(2) species coexist, which differ in their content of COX subunits and COX7A2L/HIGD2A assembly factors. The incorporation of an atypical COX1‐HIGD2A submodule attenuates supercomplex I+III(2) turnover rate, indicating an unexpected molecular adaptation for supercomplexes stabilization that relies on the presence of COX1 independently of holo‐complex IV formation. Our data set the basis for complex I structural dependence on complex IV, revealing the co‐existence of alternative pathways for the biogenesis of “supercomplex‐associated” versus individual complex IV, which could determine physiological adaptations under different stress and disease scenarios.